2012
DOI: 10.1177/0017896912439126
|View full text |Cite
|
Sign up to set email alerts
|

An observational assessment of physical activity levels and social behaviour during elementary school recess

Abstract: Objective:The purpose of the present study was to assess children's physical activity, social play behaviour, activity type and social interactions during elementary school recess using a pre-validated systematic observation system. Design: Cross-sectional. Setting: Two elementary schools located in Merseyside, England. Method: Fifty-six elementary school children (27 boys, 29 girls) were systematically observed during recess over a three-month period using a standardized physical activity observation instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
5
30
0
1
Order By: Relevance
“…This is consistent with previous research studying break time periods of the school day, in which an inverse association was reported between sedentary activities and percentage of time engaged in MVPA [64]. Whilst our analysis found that one behaviour predicted less of another, this does not imply that ST displaces PA and vice versa.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous research studying break time periods of the school day, in which an inverse association was reported between sedentary activities and percentage of time engaged in MVPA [64]. Whilst our analysis found that one behaviour predicted less of another, this does not imply that ST displaces PA and vice versa.…”
Section: Discussionsupporting
confidence: 92%
“…It is difficult to separate the effects of personal preference, sex‐related social norms, and other social influences from opportunity; additional research is needed to examine the specific mechanisms operating. It is also possible that the physical and social environments influence boys and girls differently . Furthermore, the social context, the people with whom one is physically active, may be more salient for girls than boys .…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the physical and social environments influence boys and girls differently . Furthermore, the social context, the people with whom one is physically active, may be more salient for girls than boys . Similarly, different elements of the physical environment may be salient for boys and girls …”
Section: Discussionmentioning
confidence: 99%
“…The findings from the present study may highlight an effective strategy teachers could use to engage girls in physical activity at an early age may assist with the prevention of transitional declines of physical activity into secondary school reported (Pate et al, 2007). Playing with 'unfixed equipment' has previously been associated with girls' activity within the school playground and providing further play options with unfixed equipment may encourage girls' physical activity participation (Roberts, Fairclough, Ridgers, & Porteous, 2012). As it has been reported that girls prefer engaging in social behaviour during school breaks (Roberts et al, 2012) it is possible that the social opportunities associated with introducing the intervention could be a key strategy to developing the physical activity of girls.…”
Section: Discussionmentioning
confidence: 99%
“…Within the physical environment all materials added to the array of play options except cardboard boxes (didn't last long and their use would require regular replacement) and water containers (no play purpose). Despite 'ball associated' games being regularly seen as popular by school students (Roberts et al, 2012) when play balls were introduced to the field during the LEAP intervention program, students used them as part of imaginary play and construction (e.g. cannon balls) rather than ball sports.…”
Section: Discussionmentioning
confidence: 99%